Opium consumption and long-term outcomes of CABG surgery in patients without modifiable risk factors - Sheikhy, Ali; Fallahzadeh, Aida; Nayebirad, Sepehr; Nalini, Mahdi; Sadeghian, Saeed; Pashang, Mina; Shirzad, Mahmoud; Salehi-Omran, Abbas; Mansourian, Soheil; Bagheri, Jamshid; Hosseini, Kaveh (Frontiers in Surgery, 2023)
Background The question about the significance of opium consumption as a coronary artery disease (CAD) risk factor still remains open. The present study aimed to evaluate the association between opium consumption and long term outcomes of coronary artery bypass grafting (CABG) in patients without standard modifiable CAD risk factors (SMuRFs; hypertension, diabetes, dyslipidemia, and smoking). Methods In this registry-based design, we included 23,688 patients with CAD who underwent isolated CABG between January 2006 to December 2016. Outcomes were compared in two groups; with and without SMuRF. The main outcomes were all-cause mortality, fatal and nonfatal cerebrovascular events (MACCE). Inverse probability weighting (IPW) adjusted Cox's proportional hazards (PH) model was used to evaluate the effect of opium on post-op outcomes. Results During 133,593 person-years of follow-up, opium consumption was associated with increased risk of mortality in both patients with and without SMuRFs (weighted Hazard Ratio (HR)s: 1.248 [1.009, 1.574] and 1.410 [1.008, 2.038], respectively). There was no association between opium consumption and fatal and non-fatal MACCE in patients without SMuRF (HR = 1.027 [0.762–1.383], HR 0.700 [0.438–1.118]). Opium consumption was associated with earlier age of CABG in both groups; 2.77 (1.68, 3.85) years in SMuRF-less and 1.70 (1.11, 2.38) years in patients with SMuRFs. Conclusion Opium users not only undergo CABG at younger ages but also have a higher rate of mortality regardless of the presence of traditional CAD risk factors. Conversely, the risk of MACCE is only higher in patients with at least one modifiable CAD risk factor.